EFFICACY OF PHENYTOIN IN PREVENTION OF EARLY POST-TRAUMATIC SEIZURES - Gul, Nasim; Khan, Shahbaz Ali; Khattak, Haider Ali; Muhammad, Gul; Khan, Abdul Aziz; Khan, Ibrahim; Aurangzeb, Ahsan (Journal of Ayub Medical College Abbottabad, 2019)
Background: The use of anti-epileptic drugs for prophylaxis of early post-traumatic seizures after traumatic brain injury has been very promising. The objective of this study was to determine the outcome of phenytoin in prevention of early post-traumatic seizures in moderate to severe traumatic brain injuries and to compare the frequency of seizures in moderate to severe traumatic brain injury, with phenytoin started within 12 hours and after 12 hours of injury. Methods: This cross-sectional study was conducted at Department of Neurosurgery, Ayub Medical Institute, Abbottabad from April to October, 2015. All the patients with moderate to severe head injury presenting within 48 hours of injury were included in this study in consecutive manner. Patients were started on phenytoin and observed for early post-traumatic seizures. Results: A total of 163 patients were included in this study with a mean age of 24.69±10.186 years. One hundred and twenty-two (74.8%) were males and rest of 41 (25.2%) were females. A total of 26 (16%) patients had early post-traumatic seizures. 9.89% patients in whom phenytoin was started within 12 hours had seizures, while 23.11% patients in whom phenytoin was started after 12 hours of injury had seizures, the difference being statistically significant (p-value .018). Conclusion: Frequency of early post-traumatic seizures is high in patients with moderate to severe head injured patients. Anti-epileptics like phenytoin should be started within 12 hours for seizure prophylaxis. Keywords: Phenytoin; Seizures; Early post-traumatic seizures; Prophylaxis; Brain injury; Head injury